Peel-off mask formulation from bintangur (Calophyllum inophyllum L.) leaf ethanol extract and its antibacterial activity - Liska, Liska; Amanah, Hairil; Novianti, Shindi; Mahardika, Robby Gus (Asian Journal of Health and Applied Sciences, 2022)
One of the most widely distributed plant species in Bangka Belitung is Bintangur (Calophyllum inophyllum L.) which is a genus of the Clusiaceae family. Bintagur leaf has the potential as a mask against acne-causing bacteria because it has high bioactivity such as antioxidants and antibacterials. Bitangur leaf extract masks were made by mixing the raw materials in the form of PVA 10 g; HPMC 1 g; glycerin 6 g; TEA 0.5 g; methylparaben 0.1 g; propylparaben 0.025 g; 30 ml distilled water and ethanol extract of Bintangur leaf formulation 0% 0 g; formulation 1% 0.5 g; 2% formulation 1 g and 3% formulation 1.5 g. Bintangur leaf ethanol extract mask in formulations F3 and F2 was the highest concentration producing an inhibition zone to inhibit the growth of Staphylococcus aureus and Propionibacterium acnes bacteria which were in the medium category and for formulations F1 and F3 the highest concentrations were to inhibit the growth of epidermal Staphylococcus bacteria which were categorized as The ethanol extract of Bintangur leaf whose antioxidant activity was measured obtained an IC50 value of 9.87 g/mL which was included in the very strong category. The mask of Bintangur leaf extract in the form of the peel-off gel has the potential to be used and marketed.